Semi-solid Paste Binder Dispersion in a Moving Powder Bed. (2015) - Balashanmugam, Menan; Cheong, Yuen Sin; Hounslow, Michael J.; Salman, Agba D.
Abstract: A key difference in detergent agglomeration compared to most agglomeration processes conducted in the food and pharmaceutical industries is the ultra-high viscosity of the surfactant binder. In comparison to water, these surfactants are about 1000 times more viscous. This makes handling the surfactant paste a challenge. The present study aims to understand the importance of initial binder dispersion. Experimental work has revealed how the binder deforms, breaks and assimilates in mass by gathering more powder. The rate of powder assimilation was determined as a function of the agitation intensity. At higher impeller speeds this rate is faster. The influence of the method of binder delivery on granule attributes such as size and strength was also investigated. The binder was either injected into the mixer as a stream/jet or preloaded into the mixer in the form of blobs. At moderate agitation intensity the results showed that binder injection results in faster and steadier granule growth (size), thus demonstrating the influence of binder delivery method on the kinetics of the granulation process.